PENGUASAAN KOSAKATA BAHASA JEPANG MAHASISWA ANGKATAN 2020 PRODI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Sidik, Ilham; Charlina, Charlina; Yohani, A.M. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to investigate vocabulary mastery and speakingJapanese among 2020 year students of the Japanese Language Education program atthe University of Riau. data were collected through a written test administered to 25students selected through total sampling. Statistical analysis shows the results of thewritten test reveal variations in vocabulary mastery, with the vocabulary groupingindicator having the highest percentage in the perfect qualification category (56%).Thus, this study concludes that vocabulary mastery in Japanese among 2020 yearstudents of the Japanese Language Education program at the University of Riaueducation with perfect qualifications has a percentage above 50%.Keywords: Vocabulary